Temporal transcriptome and WGCNA analysis unveils divergent drought response strategies in wild and cultivated Solanum varieties - Rajeev, Athira C.; Raju, Rajesh; Pan, Archana (Frontiers in Plant Science, 2025)
Drought, exacerbated by climate change, threatens global food security, particularly impacting crop products, including tomatoes, which are economically essential but drought sensitive. This study explores drought responses in the wild-type Solanum pennellii (WT), known for drought tolerance, and cultivated Solanum lycopersicum (CT), through RNA-Seq analysis at three drought intervals (2 Weeks +5D, +8D, and +11D). Across these points, WT and CT showed 716 and 1459 differentially expressed genes (DEGs), respectively. Pathway enrichment revealed distinct metabolic adaptations: wild varieties prioritized arginine and proline metabolism early, shifting to cutin, suberin, and wax biosynthesis by day 11, while cultivated varieties emphasized steroid biosynthesis, secondary metabolite production, and photosynthesis-related pathways. Transcription factor analysis highlighted HB-HD-ZIP enrichment in wild varieties, contrasting with broader, less coordinated TF activation in cultivated varieties. WGCNA identified the blue module as significantly associated with prolonged drought in both species. Network analysis showed ribosomal pathways enriched in CT, while in WT, it was observed broader pathway enrichment, including secondary metabolites, carbon metabolism, and oxidative stress pathways. In WT unique hub genes were, sucrose synthase and malate synthase, suggesting specialized drought adaptation mechanisms. These findings highlight multifaceted drought resilience strategy of WT compared to growth-focused response of CT, offering a foundation for breeding drought-resistant tomato varieties critical for food security under climate pressures.